82.4k views
5 votes
Write the general equation for the circle that passes through the points: (0,0) (6,0) (0,-8)

1 Answer

4 votes

Answer:


(x-3)^2+(y+4)^2=25

Explanation:

We start by writing the general form of the equation of a circle of radius R centered at
(x_0,y_0)and creating three equations (one for each unknown:
x_0,
y_0, and the radius R):


(x-x_0)^2+(y-y_0)^2=R^2

1) If the circle passes through (0,0) then we should have that the equation above holds true:


(x-x_0)^2+(y-y_0)^2=R^2\\(0-x_0)^2+(y-y_0)^2=R^2\\x_0^2+y_0^2=R^2\\R^2-x_0^2-y_0^2=0

2) If the circle passes through (6,0) then we should have that the equation above holds true, and we also can use the important result from part 1) (
R^2-x_0^2-y_0^2=0) to solve for
x_0:


(x-x_0)^2+(y-y_0)^2=R^2\\(6-x_0)^2+(y-y_0)^2=R^2\\36-12x_0+x_0^2+y_0^2=R^2\\-12x_0+36=R^2-x_0^2-y_0^2=0\\36=12x_0\\x_0=(36)/(12) =3

3) If the circle passes through (0,-8) then we should have that the general equation of the circle above holds true, and we also can use the important result from part 1) (
R^2-x_0^2-y_0^2=0) to solve for
y_0:


(x-x_0)^2+(y-y_0)^2=R^2\\(0-x_0)^2+(-8-y_0)^2=R^2\\x_0^2+64+16y_0+y_0^2=R^2\\64+16y_0=R^2-x_0^2-y_o^2=0\\16y_0=-64\\y_0=-(64)/(16)= -4

4) and finally, we use the results for
x_0 and
y_0 of parts 2) and 3) back into the equation in part 1) to solve for
R^2:


R^2-x_0^2-y_0^2=0\\R^2-(3)^2-(-4)^2=0\\R^2-9-16=0\\\R^2=9+16=25\\

Then, replacing
x_0,
y_0, and
R^2 for the values we found, the equation of the circle becomes:


(x-x_0)^2+(y-y_0)^2=R^2\\(x-3)^2+(y+4)^2=25

User Thanuja
by
5.0k points